BB Enterprise / Nurquratulnisa Muhamad Roslee ... [et al.] - Muhamad Roslee, Nurquratulnisa; Azmi, Alia Sofia Aqwa; Mohd Balinda, Siti Nur Asyiqin; Shazrul Kahar, Shazwina; Syed Zulkafli, Sharifah Nur Athirah (2023)
BB Enterprise is a company that manufactures a new invention of portable and foldable washing machine existing in the market. The company has analyzed the problem faced by the consumers when using the normal product of portable washing machine that has been introduced in the market. Our company also studied and brainstormed the product design which suitable the concepts that we decided to make it capable for consumers. The material of the product used had been decided within the company’s budget analyzed by our financial manager. The company also had done research and development in terms of idea generations and idea screening. The target market for the Aqua Washes is for the campers, travelers and students. The three groups of target markets are reaching towards portable and foldable washing machines due to the advantage offered by it. Campers and travelers who love to wash their clothes during the camping and traveling activity suitable the criteria as the target market of this type of washing machine. We believe that students need the product the most as they can save their money from washing clothes at the laundry shop.